Effect of Dietary Supplementation With Mixed Organic Acids on Immune Function, Antioxidative Characteristics, Digestive Enzymes Activity, and Intestinal Health in Broiler Chickens - Ma, Jiayu; Mahfuz, Shad; Wang, Jian; Piao, Xiangshu (Frontiers in Nutrition, 2021)
The purpose of this study was to explore the effect of dietary supplementation with mixed organic acids on intestinal health, enzyme activity and antioxidative characteristics in broilers. A total of 192 one-day-old chicks were evenly allocated to three experimental groups with eight replicates, a basal diet with 0 (Control), 3000 mg/kg (LMOA), 6000 mg/kg (HMOA) mixed organic acid. The tissue and serum samples were gathered on 21d and 42d of the experiment. An increased (P < 0.05) concentration of IgA, D-lactate (D-LA), interleukin-10 (IL-10) in the serum of broilers diets with HMOA were mainly observed. The levels of total antioxidant capacity (T-AOC) and catalase activity (CAT) in serum were enhanced (P < 0.05) dietary with mixed organic acid, respectively, and an increased (P < 0.05) content of superoxide dismutase (SOD) and CAT in the duodenum of broilers diets with LMOA were noticed. Also, LMOA decreased (P < 0.05) the pH value of duodenum and enhanced (P < 0.05) the amylase activity of the pancreas, the tight junction protein (mainly Claudin-1, Claudin-2 and ZO-1) in the duodenum of broilers fed with mixed organic acid were promoted (P < 0.05), and the LMOA group performed better in the small intestine. In cecum microbiota, LMOA and HMOA modulated the structure of microbiota and mainly reduced the relative abundance of Escherichia coli. In brief, dietary supplemented mixed organic acid improved the healthy status of broilers by promoting the immune function, enhancing the antioxidative characteristics and tight junction proteins expression as well as cecum microbiota. However, LMOA groups maybe a better fit considering the comprehensive effects of experiments and economic costs.